RAPAMYCIN INHIBITS GM-CSF-INDUCED NEUTROPHIL MIGRATION - Gomez-Cambronero, Julian (2003)
The molecular mechanisms that govern cell movement are the subject of intense study, as they impact biologically and medically important processes such as leukocyte chemotaxis and angiogenesis, among others. We demonstrate that leukocyte chemotaxis is prevented by the macrolide immunosupressant rapamycin, a specific inhibitor of the mammalian target of rapamycin (mTOR)/ribosomal p70S6 kinase (S6K) pathway. Both neutrophil chemotaxis and chemokinesis elicited by granulocyte-macrophage colony-stimulating factor (GM-CSF) were strongly inhibited by the immunosuppressant drug rapamycin with an IC(50) of 0.3 nM. Inhibition, although at a higher dose, was also observed when the chemoattractant was IL-8. As for the mechanism, rapamycin targeted the increase of phosphorylation of p70S6K due to GM-CSF treatment, as demonstrated with specific anti-p70S6K immunoprecipitation and subsequent immunoblotting with anti-T(421)/S(424) antibodies. Rapamycin also inhibited GM-CSF-induced actin polymerization, a hallmark of leukocyte migration. The specificity of the effect of rapamycin, was confirmed by the use of the structural analog FK506, which did not have a significant effect on chemotaxis but it effectively rescued rapamycin-induced p70S6K inhibition. This was expected from a competitive effect of both molecules on FK506-binding proteins (FKBP). Additionally, GM-CSF-induced chemotaxis was completely (>90%) blocked by a combination of rapamycin and the MAPK kinase (MEK) inhibitor PD-98059. In summary, the results presented here indicate for the first time that rapamycin, at sub-nanomolar concentrations, inhibits GM-CSF-induced chemotaxis and chemokinesis. This serves to underscore the relevance of the mTOR/S6K pathway in neutrophil migration.